2011
DOI: 10.1136/bmjqs.2010.046318
|View full text |Cite
|
Sign up to set email alerts
|

The influence of formulation and medicine delivery system on medication administration errors in care homes for older people

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…8,16 This definition is consistent with previously conducted studies. 5 The British National Formulary 17 was used as a reference, for example, to identify medications with food-specific administration requirements.…”
Section: Classifying Medication Administration Errorssupporting
confidence: 62%
See 1 more Smart Citation
“…8,16 This definition is consistent with previously conducted studies. 5 The British National Formulary 17 was used as a reference, for example, to identify medications with food-specific administration requirements.…”
Section: Classifying Medication Administration Errorssupporting
confidence: 62%
“…1 Alldred et al also identified in adjusted analyses of CHUMS data that there was a statistically significant doubling of the odds of a MAE for tablets and capsules administered from original packaging (OP) compared to multi-compartment compliance aid (MCA) medication administration systems (odds ratio=2.14, 95% confidence interval (CI)=1.02 to 4.51). 8 However, CHUMS was not specifically designed to compare the accuracy of medication administration between these two medication administration systems. 8 CHUMS recommended that research should be conducted into the effectiveness of MCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients can manage their own medicines with them, and supervision may be easier, or care staff can administer using MDS with the claim this is quicker and more convenient. This is partly supported by research but the evidence is incomplete 6. There are claims there is less need for additional training on medicine administration with MDS.…”
Section: What Is the Problem?mentioning
confidence: 99%
“…This increases the time taken to dispense the medicines and incurs additional staff costs 6. The repackaging may increase the chance of mistakes being made, particularly if many are done at the same time 5.…”
Section: Can Mds Cause Harm?mentioning
confidence: 99%
“…There are no reliable data about the overall cost of these devices to the NHS 11. As shown in figure 2, typically they require manual pill-by-pill filling by a dispensing technician, followed by a thorough dispensing accuracy check, in addition to the clinical check provided by the pharmacist.…”
Section: What Are Multi-compartment Mcas and How Does A Patient Get One?mentioning
confidence: 99%